IRISteg: A novel approach to improve the security of mobile banking transactions by using iris data in Steganography - Ashraf, Sameen Yasar; Hafiz, Syed Mahmud; Dip, Soumik Saha; Rahman, Lamia (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.